PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI BAGIAN PEMBANGUNAN PADA KANTOR KELURAHAN TANJUNG AGUNG BATURAJA BARAT OGAN KOMERING ULU - Rosalina, Dona (Jurnal Trisna Riset, 2025)
Organizational culture is a set of values, norms, beliefs and practices held and carried out by members of an organization. This culture reflects the way the organization operates and interacts. A strong organizational culture can influence employee behavior and motivation, which in turn has an impact on their performance in carrying out their duties and responsibilities. At the Tanjung Agung Baturaja Barat Ogan Komering Ulu Subdistrict Office, it turns out that organizational culture has not been implemented well so that employee performance is not optimal. The problem faced is how does organizational culture influence the performance of development department employees at the Tanjung Agung Baturaja Barat Ogan Komering Ulu sub-district office. The purpose of this research is to determine the influence of organizational culture on the performance of Development Department Employees at the Tanjung Agung Baturaja Barat Ogan Komering Ulu Village Office. The hypothesis proposed is that organizational culture has a positive effect on the performance of development employees at the Tanjung Agung Baturaja Barat Ogan Komering Ulu sub-district office. Data collection and processing using library studies and field studies using observation, questionnaires, interviews and documentation. From the results of calculating statistical values, the correlation between organizational culture in an effort to improve the performance of development department employees at the Tanjung Agung Baturaja Barat Ogan Komering Ulu sub-district office obtained an r figure of 0.65 after consulting conservative standards, which is between 0.600-0.799, which is included in the strong correlation. And the percentage level results show a result of 62.41%, this means that other factors that influence performance are 37.59%. So it can be said that there is a strong influence between organizational culture on the performance of Development Department Employees at the Tanjung Agung Baturaja Barat Ogan Komering Ulu Village Office.